Implementation of Social Capital Contribution of Rice Farmers in Meeting Household Needs (Case Study of Sungkai Selatan District, North Lampung Regency) from an Islamic Economic Perspective - Anggun Lestari; Fatih Fuadi; Alief Rakhman Setyanto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This research is motivated by the condition of rice farmers in South Sungkai District, North Lampung Regency, who are still facing limited financial capital in meeting household needs, so they need an alternative to social-based economic support. Social capital, which includes trust, social networks, norms, and the value of togetherness, is a non-material asset that plays an important role in the lives of farmers. This study aims to analyze the form and contribution of social capital to rice farmers in meeting household needs and review its suitability with Islamic economic perspectives. This research uses a qualitative approach with a case study method, through observation techniques, in-depth interviews, and documentation. The results of the study show that social capital makes a real contribution to meeting the needs of farmers' households, especially in the aspects of food, education, and health, through the practice of mutual cooperation, cooperation with farmer groups, and social relations based on trust and mutual help. Viewed from the perspective of Islamic economics, the practice of social capital is in line with the principles of ta'awun (help), justice, and ukhuwah (brotherhood). In conclusion, social capital not only functions as a strengthening of the economy of farmers' households, but also as a means of strengthening social solidarity and realizing sustainable prosperity in accordance with Islamic economic values.